The Impact of Traditional Marketing and Marketing Mix on Traditional Lepet Food - Lenia; Didik J Rachbini (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the role of traditional marketing in the influence of the marketing mix on awareness of traditional food products lepet. The population of this study consisted of consumers from several JABODETABEK areas, with a sample size of 288 people. The data analysis method uses the Structural Equation Model-Partial Least Square (SEM-PLS). The results found that the marketing mix and traditional marketing have an impact on awareness of traditional food lepet products. Product variants, price perception, information delivery, and moderated price perception are variants that are able to encourage consumers to know the product directly. However, other marketing mixes variable are not able to encourage product awareness.